Motor protein function in skeletal muscle-a multiple scale approach to contractility. - von Wegner, Frederic; Schürmann, Sebastian; Fink, Rainer; Vogel, M.; Friedrich, Oliver (IEEE transactions on medical imaging, 2009)
We present an approach to skeletal muscle contractility and its regulation over different scales ranging from biomechanical studies in intact muscle fibers down to the motility and interaction of single motor protein molecules. At each scale, shortening velocities as a measure for weak cross-bridge cycling rates are extracted and compared. Experimental approaches include transmitted light microscopy, second harmonic generation imaging of contracting myofibrils, and fluorescence microscopy of single molecule motility. Each method yields image sequences that are analyzed with automated image processing algorithms to extract the contraction velocity. Using this approach, we show how to isolate the contribution of the motor proteins actin and myosin and their modulation by regulatory proteins from the concerted action of electro-mechanical activation on a more complex cellular scale. The advantage of this approach is that averaged contraction velocities can be determined on the different scales ranging from isolated motor proteins to sarcomere levels in myofibrils and myofibril arrays within the cellular architecture. Our results show that maximum shortening velocities during in situ electrical activation of sarcomere contraction in intact single muscle cells can substantially deviate from sliding velocities obtained in oriented in vitro motility assays of isolated motor proteins showing that biophysical contraction kinetics not simply translate linearly between contractility scales. To adequately resolve the very fast initial mechanical activation kinetics of shortening at each scale, it was necessary to implement high-speed imaging techniques. In the case of intact fibers and single molecule motility, we achieved a major increase in temporal resolution up to frame rates of 200-1000 fps using CMOS image sensor technology. The data we obtained at this unprecedented temporal resolution and the parameters extracted can be used to validate results obtained from computational models of motor protein interaction and skeletal muscle contractility in health and muscle disease. Our approach is feasible to explain the possible underlying mechanisms that contribute to different shortening velocities at different scales and complexities.
Keywords: biomechanics; biomedical optical imaging; cellular biophysics; high-speed optical techniques; molecular biophysics; muscle; optical microscopy; proteins